FRIS Revisited in 2018: On the Circulation and Water Masses at the Filchner and Ronne Ice Shelves in the Southern Weddell Sea - Janout, Markus A; Hellmer, Hartmut H; Hattermann, Tore; Huhn, Oliver; Sültenfuss, Jürgen; Østerhus, Svein; Stulic, Lukrecia; Ryan, Svenja; Schröder, Michael; Kanzow, Torsten (Journal of Geophysical Research: Oceans, 2021)
The Filchner-Ronne Ice Shelf (FRIS) is characterized by moderate basal melt rates due to the near-freezing waters that dominate the wide southern Weddell Sea continental shelf. We revisited the region in austral summer 2018 with detailed hydrographic and noble gas surveys along FRIS. The FRIS front was characterized by High Salinity Shelf Water (HSSW) in Ronne Depression, Ice Shelf Water (ISW) on its eastern flank, and an inflow of modified Warm Deep Water (mWDW) entering through Central Trough. Filchner Trough was dominated by Ronne HSSW-sourced ISW, likely forced by a recently intensified circulation beneath FRIS due to enhanced sea ice production in the Ronne polynya since 2015. Glacial meltwater fractions and tracer-based water mass dating indicate two separate ISW outflow cores, one hugging the Berkner slope after a two-year travel time, and the other located in the central Filchner Trough following a ∼six year-long transit through the FRIS cavity. Historical measurements indicate the presence of two distinct modes, in which water masses in Filchner Trough were dominated by either Ronne HSSW-derived ISW (Ronne-mode) or more locally derived Berkner-HSSW (Berkner-mode). While the dominance of these modes has alternated on interannual time scales, ocean densities in Filchner Trough have remained remarkably stable since the first surveys in 1980. Indeed, geostrophic velocities indicated outflowing ISW-cores along the trough's western flank and onto Berkner Bank, which suggests that Ronne-ISW preconditions Berkner-HSSW production. The negligible density difference between Berkner- and Ronne-mode waters indicates that each contributes cold dense shelf waters to protect FRIS against inflowing mWDW.
Keywords: Sørishavet; Weddellhavet; oseanografi; vannmasser

Basal Melt and Freezing Rates From First Noble Gas Samples Beneath an Ice Shelf - Huhn, Oliver; Hattermann, Tore; Davis, Peter E D; Dunker, Erich; Hellmer, Hartmut H; Nicholls, Keith W; Østerhus, Svein; Rhein, Monika; Schröder, Michael; Sültenfuß, Jürgen (Geophysical Research Letters, 2018)
A climatically induced acceleration in ocean-driven melting of Antarctic ice shelves would have consequences for both the discharge of continental ice into the ocean and thus global sea level, and for the formation of Antarctic Bottom Water and the oceanic meridional overturning circulation. Using a novel gas-tight in situ water sampler, noble gas samples have been collected from six locations beneath the Filchner Ice Shelf, the first such samples from beneath an Antarctic ice shelf. Helium and neon are uniquely suited as tracers of glacial meltwater in the ocean. Basal meltwater fractions range from 3.6% near the ice shelf base to 0.5% near the sea floor, with distinct regional differences. We estimate an average basal melt rate for the Filchner-Ronne Ice Shelf of 177 ± 95 Gt/year, independently confirming previous results. We calculate that up to 2.7% of the meltwater has been refrozen, and we identify a local source of crustal helium.
Keywords: Sørishavet; Weddellhavet; bunnvann; glasiologi; havnivå; innlandsis; isbrem; klimatologi; oseanografi; smelting; vannmasser

The Weddell Gyre, Southern Ocean: Present Knowledge and Future Challenges - Vernet, M; Geibert, Walter; Hoppema, Mario; Brown, Peter J; Haas, Christian; Hellmer, Hartmut H; Jokat, Wilfried; Jullion, L; Mazloff, M; Bakker, D C E; Brearley, J A; Croot, Peter L; et al. (Reviews of Geophysics, 2019)
The Weddell Gyre (WG) is one of the main oceanographic features of the Southern Ocean south of the Antarctic Circumpolar Current which plays an influential role in global ocean circulation as well as gas exchange with the atmosphere. We review the state-of-the art knowledge concerning the WG from an interdisciplinary perspective, uncovering critical aspects needed to understand this system's role in shaping the future evolution of oceanic heat and carbon uptake over the next decades. The main limitations in our knowledge are related to the conditions in this extreme and remote environment, where the polar night, very low air temperatures, and presence of sea ice year-round hamper field and remotely sensed measurements. We highlight the importance of winter and under-ice conditions in the southern WG, the role that new technology will play to overcome present-day sampling limitations, the importance of the WG connectivity to the low-latitude oceans and atmosphere, and the expected intensification of the WG circulation as the westerly winds intensify. Greater international cooperation is needed to define key sampling locations that can be visited by any research vessel in the region. Existing transects sampled since the 1980s along the Prime Meridian and along an East-West section at ~62°S should be maintained with regularity to provide answers to the relevant questions. This approach will provide long-term data to determine trends and will improve representation of processes for regional, Antarctic-wide, and global modeling efforts—thereby enhancing predictions of the WG in global ocean circulation and climate.
Keywords: Sørishavet; Weddellhavet; biologi; brehylle; geologi; havis; havstrømmer; isbrem; isshelf; kjemi; oseanografi; sjøis; vannmasser; vannvirvler

Wind-driven upwelling of iron sustains dense blooms and food webs in the eastern Weddell Gyre - Moreau, Sebastien; Hattermann, Tore; de Steur, Laura; Kauko, Hanna M.; Ahonen, Heidi; Ardelan, Murat; Assmy, Philipp; Chierici, Melissa; Descamps, Sebastien; Dinter, Tilman; Falkenhaug, Tone; Fransson, Agneta; et al. (Nature Communications, 2023)
The Southern Ocean is a major sink of anthropogenic CO2 and an important foraging area for top trophic level consumers. However, iron limitation sets an upper limit to primary productivity. Here we report on a considerably dense late summer phytoplankton bloom spanning 9000 km2 in the open ocean of the eastern Weddell Gyre. Over its 2.5 months duration, the bloom accumulated up to 20 g C m−2 of organic matter, which is unusually high for Southern Ocean open waters. We show that, over 1997–2019, this open ocean bloom was likely driven by anomalies in easterly winds that push sea ice southwards and favor the upwelling of Warm Deep Water enriched in hydrothermal iron and, possibly, other iron sources. This recurring open ocean bloom likely facilitates enhanced carbon export and sustains high standing stocks of Antarctic krill, supporting feeding hot spots for marine birds and baleen whales.
Keywords: Sørishavet; kjemi; marin biologi; oseanografi; plankton